On Derksen’s law and related issues - Kortlandt, Frederik (Baltistica, 2012)
Dominant suffixes in Baltic and Slavic originated from retractions of the stress or later extensions and some of them arose in the Balto-Slavic period already. The retraction of the stress in Lith. dùkterį may or may not have been a phonetic development.
Keywords: Derksen's law; Balto-Slavic; historical acentology; accentuation; dominant suffixes